Unpacking Joint Decision-making - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Improving women’s decision-making power is crucial for advancing gender equality. But evidence shows that wives and husbands have systematically different perceptions of who makes these decisions across contexts and intra-household disagreement is often not random; women “taking power” correlates with other women’s empowerment variables. This could be because the standard decision-making answer options “wife, husband, joint” is too categorical and it does not allow us to capture the strength in decision-making power (thinking it as a continuum), or because men and women have a different understanding of what sole/joint decision-making is. This tool, Unpacking Joint Decision-making, allows us to elicit responses regarding subjective assessments of a hypothetical married couple under different scenarios that involve the wife and the husband making household decisions around large household purchases. This tool is suited for nationally representative individual- or household-level surveys, and for targeted thematic or impact evaluation surveys designed to understand individuals' agency and decision-making. This data study includes following files. 1. A survey document (including implementation guidelines) 2. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.